PENGARUH CARA TANAM KEDELAI DAN DOSIS NITROGEN PADA TANAMAN KAPAS TERHADAP PERKEMBANGAN HAMA DAN HASIL KAPAS - SAHID, MOCH.; CHOLID, MOHAMMAD; YULIANTI, TIT1EK (Jurnal Penelitian Tanaman Industri, 2000)
The effect of soybean planting methods and dosage of nitrogen fertilizer for cotton on pest development and cotton yieldThe effect of soybean planting methods and dosage of N fertilizer for cotton on pests development and cotton yield was studied in Tanggungan, Pucuk, lanongan from July 1997 to March 1998 on wet land previousl grown with rice plant rice. Split plot design in three replicates was used, planting system of soybean (sowed and planted in a hole) was the main plot and the rate of N fertilizer (30 kg N/ha, 60 kg N/ha and 90 kg N/ha) was the sub plot. Urea and ZA were used as source of N; SP36 for P20, and KCI for KjO. The rate of SP36 was 50 kg/ha and KCI was 50 kg/ha. One third of the full dosage of N (ZA) and the full dosage of P]Oj (SP36) and K20 (KCI) were applied at the time of planting While 2/3 of N were applied 6 weeks after planting. Cotton variety used in this study was ISA 205 A and soybean was Willis. Cropping pattern was 2 rows of cotton and 5 rows of soybean. Planting space of cotton was (190) 60 cm x 30 cm (2 plants per hole), hence the population was 53 280 plants per hectare. Plant spacing of soybean was 30 cm x 20 cm (2 plant per hole), hence the population was 200 000 plants per hectare. Parameters evaluated were the growth of cotton plant (height and canopy); component of yield (vegetative and generative branch, square shedding and number of bolls), and population of pest. The results showed that increasing the dosage of N from 30 (50% of the recommended dosage) to 60 kg (recommended dosage) and 90 kg (150% of the recommended) resulted in increased population of H. armigera from 12.33 insect to 18.77 and 17.00 insect, Erias sp. from 93.17 to 51.50 and 51.50 and S. bigutulla fom 103.5 to 102.50 and 122.30 insects per plant. Increased population of pest was followed by increased frequency of spraying from 2.50 to 3.50 and 3.67 times. Application of 30 kg N/ha decreased the population of// armigera, Earias sp. and 5. biguttula. however, the highest yield of cotton (1 580.16 kg/ha) was gained by applying 60 kg N/ha. Soybean planted by broascasting method had greater effect on cotton and soybean yields than dibbling method.